COMBINATION OF THE COMMUNICATIVE APROACH, INTENSIVE TECHNIQUE AND EMOTIONAL-SEMANTIC METHOD IN TEACHING FOREIGN LANGUAGES - Kushakov, Yusup (Журнал иностранных языков и лингвистики, 2023)
In this article, the problems of combination of the main approaches, technique and emotional –semantic methods in teaching foreign languages are considered as basic factors in the educational process. According to the author, teachers need to take into account all these factors in explaining new language material. The author highlights the basic points in this sphere.